A Simple Device Based on Smart Hollow Microgels for Facile Detection of Trace Lead(II) Ions. Issue 16 (17th April 2018) - Wang, Yuan; Liu, Zhuang; Peng, Han‐Yu; He, Fan; Zhang, Lei; Faraj, Yousef; Wang, Wei; Ju, Xiao‐Jie; Xie, Rui; Chu, Liang‐Yin
Abstract: A simple device, which is equipped with a non‐woven fabric filter medium immobilized with ion‐recognizable smart hollow microgels, is developed for facile detection of trace lead(II) ions (Pb 2+ ). The ion‐recognizable smart microgels are made of poly( N ‐isopropylacrylamide‐ co ‐benzo‐18‐crown‐6‐acrylamide) (PNB), in which the 18‐crown‐6 groups act as the sensors of Pb 2+ and the N ‐isopropylacrylamide groups act as the actuators. The PNB hollow microgels can isothermally change from a shrunk state to a swollen state in response to recognizing Pb 2+ in the aqueous environment due to the electrostatic repulsion among the charged 18‐crown‐6/Pb 2+ complex groups and the enhancement of hydrophilicity of the microgels. Due to the hollow structures, the PNB microgels show remarkable isothermal swelling ratio. Thus, the flux of solution pass through the non‐woven fabric filter medium decreases significantly because of the remarkable reduction in the space for liquid flowing upon recognizing Pb 2+ . The Pb 2+ concentration can be detected quantitatively by simply and easily measuring the change of solution flux using the proposed device, which is operated without external power supply or spectroscopic measurements. The strategy proposed in this study provides a promising method for facile detection of trace Pb 2+ in aqueous environments. Abstract : Smart detection : Ion‐recognizable hollow microgels with outer diameters ranging from 3 to 5 μm are successfully prepared, and are immobilized on non‐woven fabric filter medium to develop a simple device for facile detection of trace lead(II) ions in aqueous environments.